Analyzing of Using Educational Technology to Improve the Quality and Equity of Learning Outcomes at Politeknik Maritim Negeri - Sri Tutie Rahayu (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aimed to identify the use of educational technology in supporting the education of the next generation who want to improve the quality and equity of learning outcomes. The researcher carried out a series of data collection at one of the tertiary institutions, namely the Indonesian state maritime polytechnic. The researcher obtained the needed data through the location observation interview approach and documentation. Next, it analyze uding a phenomenological approach. The secondary and primary data coding was checked, organized, organized, and finally interpreted to get relevant and valid conclusions to answer this study's problems. After a series of analyses and discussion of data, this study concludes that there were several use for technology to support activities and accelerate learning at the Indonesian State Maritime Polytechnic, including that technology has become a core in learning because the power of innovation and revolution provides equity learning result in student learning. These various features and technology platforms enabled very effective and innovative learning, such as in efforts to develop the quality of lecturers with a variety of choices for learning or artificial intelligence to enable learning to occur more autonomously and accelerate training models and other classroom exercises. The study's results provide additional information for similar studies in the future. Keywords: Equity Learning Outcome, Quality Learning Outcome, Educational Technology